Evaluation of Factors of Design Change, Material Availability and Labor Productivity Against Cost Performance on Office Building Projects - Endawati Endawati; Budi Susetyo (International Journal Labs, 2023)
Good cost performance will result in profit margins for the company, but on the contrary, poor cost performance will certainly result in cost overruns. And this is often and even always the case with every project, both in construction projects and office building projects. Several factors can influence the decline in cost performance so that there is a cost overrun, such as design changes, material availability, work improvements, poor labor relations, incomplete project documents, increase in material prices, labor, equipment, project finances, and project implementation time. With the various causes of decreased cost performance, this research will limit the analysis of factors such as changes in design, material availability and labor productivity, which are indeed very frequent in construction projects, especially in office building projects. Office building projects are not as large as high-rise construction projects or other civil projects, but in terms of the complexity of detailed types of work, it is often a boomerang for cost overruns. This study used a statistical analysis approach using an SPSS device based on questionnaire data for implementing contractors in Jakarta.